Conveying Islamic Teachings to Converts Through Problem Solving: A Study on the Efforts to Revitalize Female Converts - Cucu, Cucu; Waldan, Raziki; Abdullah, Johari bin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2024)
This study aims to explore the dissemination of Islamic teachings to female converts through an innovative approach focusing on the revitalization of faith, economic empowerment, and mental health improvement. Utilizing a qualitative case study method, data were collected through in-depth interviews with the management of Rumah Quran Assiradj, female convert congregants, and community leaders, complemented by observation and documentation. The findings highlight the success of Islamic preaching in strengthening faith (tauhid), religious understanding, and worship practices among female converts, contributing to the development of noble character. Togetherness in study sessions fosters economic independence, while religious guidance helps reduce mental dependence. The implications of this study emphasize a collaborative preaching model between female converts and Rumah Quran as an effective approach to fortify faith, promote economic self-reliance, and enhance the mental well-being of female converts.